S09.1 Incidence and prevalence of systemic lupus erythematosus in a large population-based study in northeastern Italy, between 2012 and 2020. (27th September 2022) - Zen, M; Salmaso, L; Barbiellini Amidei, C; Fuzzi, E; Fedeli, U; Bellio, S; Iaccarino, L; Saia, M; Doria, A
Abstract : Objectives: Incidence and prevalence of SLE widely vary across different countries, being influenced by study design, population demographics, and ethnicity. Four studies evaluated the epidemiology of SLE in Italy: they covered a short period of time (4 year at most), two of them were published more than fifteen years ago, and they all involved a small number of participants (112, 365, 346, 000, 71, 204, and 25, 885 individuals as the general population screened, respectively). 1–4 We aimed at estimating the incidence and prevalence of SLE in northeastern Italy over the period 2012–2020. Methods: A retrospective population-based study was conducted in Veneto Region using the Population Registry, an administrative health database where all residents are recorded (about 4.9 million people). The population registry was linked with healthcare co-payments exemptions, hospital discharge records, and mortality records. SLE was defined by any hospital diagnosis of SLE (ICD-9-CM 710.0) or a healthcare copayment exemption for SLE (national registry code 028). Standardized incidence and prevalence were estimated per 100, 000 people in the period 2012–2020, stratified by age, gender, and year. Results: During the study period, we identified 4, 283 prevalent cases with SLE (85% female) of whom 1092 were incident cases. SLE incidence was 2.8 per 100, 000 (95%CI 2.6–2.9), with an annual decline of 8% (p<0.0001). Incidence was 5-times higher among females (sex incidence rate ratio: 5.00 95% CI 4.25–5.87 p<0.0001), with a peak at 30–39 years for women. At diagnosis, women were significantly younger (45 years, IQR 33–58) than men (52, IQR 38–64). SLE standardized point prevalence increased from 66.7/100, 000 (95%CI 64.3–69.0) in 2012 to 72.9/100, 000 residents (95% CI 70.5–75.3) in 2020, with an annual increment of 1.4% (p<0.0001). The highest prevalence rate was observed in females aged 60–69 years. Conclusions: Over the last 9 years, in northeastern Italy, SLE incidence has declined, while prevalence has increased in both sexes. SLE onset occurred earlier in life among women and was significantly more common in women compared to men. The highest incidence was observed among females aged 30–39 years. References: Tsioni V, Andreoli L, Meini A, et al. Clin Exp Rheumatol 2015;33 (5):681–7. Govoni M, Castellino G, Bosi S, et al. Lupus 2006;15 :110–3. Benucci M, Del Rosso A, Li Gobbi F, et al. Med Sci Monit 2005;11 :CR420–5. Sardu C, Cocco E, Mereu A, et al. PLoS One 2012;7 :e32487.